VEIN OF GALEN ANEURISMAL MALFORMATION: DIAGNOSIS CONFIRMED ON MRI AND CT ANGIOGRAPHY- A CASE REPORT OF 2.5 YEARS OLD CHILD AND REVIEW OF THE LITERATURE. - Saeed Mazher; Junaid Ashraf et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: In this uncommon case report, we present a case of 2.5years old child with Vein of Galen Malformation who presented with history of headache used to relieve by taking analgesics. The purpose of this report is to increase the awareness about this challenging diagnostic dilemma demanding early recognition and decrease morbidity and mortality.